The European Union and the South Caucasus in the Context of the Energy Crisis - Igor M. Uznarodov; Viktor V. Klochkov (Кавказология, 2023)
The XXI century has witnessed the European Union's heightened focus towards transitioning to an eco-friendly economy rooted in energy sector that is both efficient and environmentally sustainable. In spite of the ongoing efforts, an energy crisis commenced on the European continent in 2021. This was caused by the swift substitution of hydrocarbon energy carriers with renewable energy sources and the sudden cessation of nuclear energy. The situation has been significantly worsened by anti-Russian sanctions and bans on the import of Russian energy carriers.The article shows the main milestones of the EU’s general policy towards the states of the South Caucasus in the XXI century, discusses the plans of the EU leadership to use the energy resources of the South Caucasus to bring the energy sector out of the current crisis. Azerbaijan’s export opportunities in terms of energy carriers are analyzed, as well as the role of Georgia and Turkey as transit states. The presence of serious problems related to the capacity of existing oil and gas pipelines has been revealed. It is concluded that Azerbaijani energy carriers will not be able to replace Russian ones in the near future.